Hyperuricemia predicts adverse clinical outcomes after arthroscopic microfracture of osteochondral lesions of the talus - Yuanqiang Li; Zhenyu Wang; Guo Zheng; Lin Ma; Xin Xin Li; Yan Liang; Xinyu Xie; Xiaolin Zhang; Chengsong Yuan; Wan Chen (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2025)
Purpose: To investigate the correlation of serum uric acid levels with the clinical outcomes of arthroscopic microfracture in osteochondral lesions of the talus (OLTs) and determine the cut-off point for predicting outcomes. Methods: A total of 134 OLTs patients who underwent arthroscopic microfracture from November 2008 to June 2019 were included: 42 in the hyperuricemia group (≥ 420 μmol/L) and 92 in the non-hyperuricemia group (< 420 μmol/L). Clinical characteristics recorded and analyzed included Visual Analog Scale (VAS score), American Orthopaedic Foot & Ankle Society score (AOFAS), and 36-Item Short Form Health Survey score (SF-36). Logistic regression identified risk factors, and Receiver Operating Characteristic Curves (ROC) determined the serum uric acid cut-off value for predicting outcomes, which was prospectively validated. Results: Significant improvement were observed in postoperative range of motion score, VAS score, AOFAS score, and SF-36 score across all patients (P < 0.05). However, the VAS score for the non-hyperuricemia group was lower; In contrast, the AOFAS and SF-36 scores were higher than the hyperuricemia group during the last visit (P < 0.05). Multivariate analysis identified age, serum uric acid, osteochondral defect size, and urate deposition as independent risk factors for clinical outcomes, and the cut-off value for the serum uric acid American Orthopaedic Foot & Ankle Society score 445 μmol/L with sensitivity and specificity of 87.25 % and 81.25 %, respectively. Additionally, the derivation set demonstrated a sensitivity of 85.71 % and specificity of 83.33 % in predicting poor outcomes. Conclusion: Hyperuricemia predicts adverse clinical outcomes after arthroscopic microfracture of osteochondral lesions of the talus, strict postoperative drop uric acid treatment, especially hyperuricemia OLTs serum uric acid levels ≥ 445μmol/L. Level of evidence: Level IV, case series.